Hurricane Season - Melchor, Fernanda, 1982-; Hughes, Sophie, (Sophie Elizabeth), 1986- (New York : New Directions Publishing Corporation, 2020)
"The Witch is dead. And the discovery of her corpse-by a group of children playing near the irrigation canals-propels the whole village into an investigation of how and why this murder occurred. Rumors and suspicions spread. As the novel unfolds in a dazzling linguistic torrent, with each unreliable narrator lingering details, new acts of depravity or brutality, Melchor extracts some tiny shred of humanity from these characters that most would write off as utterly irredeemable, forming a lasting portraitof a damned Mexican village. Like Roberto Bolaño's 2666 or Faulkner's greatest novels, Hurricane Season takes place in a world filled with mythology and violence-real violence, the kind that seeps into the soil, poisoning everything around: it's a worldthat becomes more terrifying and more terrifyingly real the deeper you explore it"--.
"Originally published in Spanish as Temporada de huracanes"--Title page verso.
new book 2024 summer.
Translated from Spanish.
Keywords: Mythology -- Fiction; Violence -- Fiction; Villages; Superstition; Mexico; Dystopian fiction; Mythology